Public-Sector Productivity (Part 1) : Why Is It Important and How Can We Measure It? - Somani, Ravi (World Bank, Washington, DC, 2021)
This note is the first of a two-part series that explores the importance of public-sector productivity and its measurement (part one); and its determinants (part two). This note summarizes a review of the literature on different approaches to measuring public-sector productivity (the rate at which inputs are converted into outputs). This note recommends: complementing traditional `macro’ measures of public-sector productivity, such as the cost-weighted-output approach presented in Atkinson (2005), with fine-grained `micro’ measures at the individual organization, employee, and task and process level; monitoring and reporting output (performance) measures and inputs (costs) separately; and combining multiple measures of productivity, tied closely to the service-delivery chain.